Enhanced optical activity of atomically thin MoSe2 proximal to nanoscale plasmonic slot-waveguides. (8th February 2017) - Blauth, M; Harms, J; Prechtl, M; Finley, J J; Kaniber, M
Abstract: The ever increasing demand of computational power has led to significant scientific interest in optical interconnects due to higher achievable bandwidth and reduced energy consumption per bit. However, the diffraction limit poses ultimate device size limits for conventional photonics that can potentially be circumvented by exploiting nano-plasmonic effects to achieve deep-subwavelength optical confinement. Integrable efficient light sources are key requirements for on-chip plasmonic interconnects and recently, monolayer transition metal dichalcognides (TMDs) have shown significant potential for the use as high efficiency optical emitters at room temperature due to their direct bandgap, extremely high exciton binding energies and large quantum efficiency. First studies on coupling plasmonic waveguides and TMD flakes have demonstrated plasmonic excitation and guiding of light. We show a 2 × enhancement of the photoluminescence intensity for a hybrid system consisting of a MoSe2 monolayer and lithographically fabricated nano-plasmonic slot waveguides. Beside this indication of enhanced light-matter interaction, the plasmonic guiding of light in strongly sub-wavelength waveguide modes exhibiting a transverse mode area of 0.02 λ 2 with propagation lengths of ( 380 ± 60 ) nm is demonstrated. The integration of 2D materials with deterministic routing paves the way toward novel small footprint, deep-subwavelength on-chip light sources.